(untitled) (Journal of Nematode Morphology and Systematics, 2010)
Two species of Aquatides Heyns, 1968, recovered from soil or sediment samples in different localities and aquatic habitats of peninsular Spain, are studied. Descriptions, measurements and illustrations of A. aquaticus (Thorne, 1930) Thorne, 1974 and A. ibericus sp. n. are presented, and a comparison with previous descriptions of A. aquaticus and comments on its morphological features are given. A key to the nominal species of the genus Aquatides is also given. A. ibericus sp. n. is characterized by its body 2.2-2.9 mm long in females and 1.9-2.7 mm long in males; lip region not truncate, subangular, and separated from adjacent body only by a slight depression; mural tooth linear but approximating deltoid type, about 14-18 μm long; uterus without specializations, pars distalis vaginae with straight or slightly plicate walls, pars refringens vaginae absent, pars proximalis vaginae with expanded contour, vulva transverse, prerectum relatively short, tail bluntly convex-conoid and 36-54 μm long, and spicules 57- 7 μm long.